2020
DOI: 10.1002/prp2.641
|View full text |Cite
|
Sign up to set email alerts
|

Medication‐related problems and adverse drug reactions in Ethiopia: A systematic review

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
1
15
1
Order By: Relevance
“…Thus far only a few studies have investigated medicinal plant use [3,19,[147][148][149] and prescription medicine use or self-medication practice during pregnancy [28,38,47,[150][151][152][153][154] in Ethiopia, however, all were conducted among outpatient women, mainly in their early stage of pregnancy, and failed to capture the full picture of use of the various treatment modalities in the entire pregnancy. Likewise, though some MRP identification studies have been conducted among inpatients so far in Ethiopia [155][156][157][158][159], all have focused on the non-pregnant patient population. Thus far, no study has investigated MRPs in pregnant and lactating inpatients in a hospital setting in Ethiopia.…”
Section: Rationale Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far only a few studies have investigated medicinal plant use [3,19,[147][148][149] and prescription medicine use or self-medication practice during pregnancy [28,38,47,[150][151][152][153][154] in Ethiopia, however, all were conducted among outpatient women, mainly in their early stage of pregnancy, and failed to capture the full picture of use of the various treatment modalities in the entire pregnancy. Likewise, though some MRP identification studies have been conducted among inpatients so far in Ethiopia [155][156][157][158][159], all have focused on the non-pregnant patient population. Thus far, no study has investigated MRPs in pregnant and lactating inpatients in a hospital setting in Ethiopia.…”
Section: Rationale Of the Studymentioning
confidence: 99%
“…Particularly, studies have indicated that chronic disease patients are more likely to use multiple medications making them prone to drug-drug interactions predisposing women to MRPs [159]. Therefore, intervention measures to reduce the harmful effects of medicines and herbs on pregnancy should consider this interrelated nature of predictor and outcome variables and focus on these prioritized areas.…”
Section: Factors Associated With Use Of Treatment Modalities and Mrpsmentioning
confidence: 99%
“…The most important independent factor underlying non-compliance to treatment is adverse events of medications ( Resende and Santos-Neto, 2015 ; Merid et al, 2019 ; Sankar et al, 2021 ). The overall incidence of ADEs caused by anti-TB medications ranges from 5.1% to 83.5% in different populations ( Kefale et al, 2020 ). ADEs increase patient suffering and increase substantial additional costs because of added outpatient visits, laboratory investigations, and hospitalizations, in more serious instances ( Resende and Santos-Neto, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] According to a systematic review on the prevalence of medicationrelated problems and ADRs, the overall median prevalence of ADRs in Ethiopia is 36.6% with a range of 10.0 to 85.7%. 10 A prospective cross-sectional study conducted in Southwest Ethiopia also reported that ADRs were a common cause of hospitalization and are a reason for the high in-hospital mortality rate. 11 Maintaining and monitoring drugs efficacy and safety is a critical point in clinical practice.…”
Section: Introductionmentioning
confidence: 99%